Been it - The Cardigans; Stockholm Records (Sweden : Stockholm Records, 1996)
Contains the single taken from the album First Band On The Moon.
CD 1 : Been It (censored radio edit) / (3:41)
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English